PERAN CORPORATE SOCIAL RESPONSIBILITY MEMODERASI HUBUNGAN PROFITABILITAS, LEVERAGE, CAPITAL INTENSITY DENGAN TAX AVOIDANCE - Putu Purnama Dewi; Ni Putu Ananda Putri Ayu Ningrat Permata Dewi (KRISNA: Kumpulan Riset Akuntansi, 2025)
This research aims to examine the role of corporate social responsibility as a moderating variable in influencing the relationship between profitability, leverage, and capital intensity with tax avoidance. This research uses agency theory as a foundation in the practice of tax avoidance conducted by companies. This is a quantitative research using secondary data from annual reports and sustainability reports of companies with a population of companies covering the banking sub-sector listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Based on purposive sampling, 177 samples from 43 companies were obtained. The data analysis used in this research is panel data regression using STATA 16 software. The results of the analysis show that profitability, leverage, and capital intensity have a positive significant effect on tax avoidance. The results also show that corporate social responsibility can moderate profitability and capital intensity by providing a positive significant effect on tax avoidance but corporate social responsibility cannot strengthen the moderation of leverage by providing a negative significant effect on tax avoidance